Vacuum-assisted closure (VAC) for craniocerebral wounds in severely injured patients: technical note of a damage control procedure. Issue 6 (December 2019) - Joubert, Christophe; Sellier, A; Morvan, J-B; Beucler, N; Bordes, J; Dagain, A
Abstract : The management of a craniocerebral wound (CCW) remains challenging, particularly in a severely injured patient. Considering the complexity of the multilayer insult and damage control care in an unstable patient, every procedure performed should promptly benefit the patient. We report an illustrative case of a patient with a gunshot wound to the head that resulted in a CCW for which we applied vacuum-assisted closure (VAC) therapy according to damage control principles. We describe the technical approach and discuss the indications, results and technique by considering the literature available. VAC can be used for CCWs, particularly for large defects in selected patients according to clinical and CT evaluations following immediate resuscitation. In severely injured and unstable patients, VAC aims to delay definitive reconstructive and time-consuming treatment. Interestingly, it appears to be a safe treatment based on the previously described—but not exclusively trauma—cases with no secondary cerebrospinal fluid leakage encountered.